Q: How would you simplify 5x2 plus 9x-2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is 4x^2 + 10x - 1

Answer this question…A. x4 + 2x3 + 9x2 + 4 B. x4 + 4x3 + 9x2 + 4 C. x4 + 2x3 + 9x2 + 4x + 4 D. x4 + 2x3 + 9x2 - 4x + 4

-5y2+3x+2y

9x2+9x-12 All I can do is simplify this. I can't solve it unless turn this expression into an equation.

If you mean: f(x) = x4 - 3x3 + 5x2 / x2 then: f(x) = x4 - 3x3 + 5 ∴ f'(x) = 4x3 - 9x2 If you mean: f(x) = (x4 - 3x3 + 5x2) / x2 then: f(x) = x2 - 3x + 5 ∴ f'(x) = 2x - 3

Related questions

It is 4x^2 + 10x - 1

Answer this question…A. x4 + 2x3 + 9x2 + 4 B. x4 + 4x3 + 9x2 + 4 C. x4 + 2x3 + 9x2 + 4x + 4 D. x4 + 2x3 + 9x2 - 4x + 4

-5y2+3x+2y

9x2+9x-12 All I can do is simplify this. I can't solve it unless turn this expression into an equation.

If you mean: f(x) = x4 - 3x3 + 5x2 / x2 then: f(x) = x4 - 3x3 + 5 ∴ f'(x) = 4x3 - 9x2 If you mean: f(x) = (x4 - 3x3 + 5x2) / x2 then: f(x) = x2 - 3x + 5 ∴ f'(x) = 2x - 3

= 53 9x3 + 9x2 + 5x1+ 3x1 27 + 18 + 5 + 3

9x2 + 12x + 4 = 9x2 + 6x + 6x + 4 = 3x(3x + 2) + 2(3x + 2) = (3x + 2)(3x + 2) = (3x + 2)2

9x2

9x2 + 9x - 10 =(3x - 2)(3x + 5)

(9x2 + 7)(9x2 - 7) = 81x4 - 49

16? using 16, you have (3x2 + 4)(3x2 + 4) = 9x2 + 24x + 16

9x2+2x-7 = (9x-7)(x+1) when factored